2021
DOI: 10.1002/lno.11921
|View full text |Cite
|
Sign up to set email alerts
|

How do fisher responses to macroalgal overgrowth influence the resilience of coral reefs?

Abstract: Many coral reefs have shifted from coral-to macroalgae-dominated community states, heightening the need to understand resilience of coral communities. Fishing on herbivores often reduces resilience of the coral state, as lower herbivory fosters macroalgal establishment. Despite the acknowledged importance of fishing, relatively little attention has been paid to how fishers change their behavior as macroalgae overgrow reefs, or how the resulting dynamic feedbacks might affect resilience. We address these questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Fishing often generates a cascade of indirect effects that can alter community structure, ecosystem function, and resilience. Lagged responses between trophic levels (e.g., herbivores and primary producers) can create nonlinear community dynamics by promoting thresholds and tipping points (Salomon et al, 2009), potentially triggering an abrupt regime shift to a degraded state (Frank et al, 2005; Österblom et al, 2007; Rassweiler et al, 2022). Our model reveals that resilience of corals on coral reefs is not only affected by the intensity at which fishers harvest herbivores but also by the type of herbivore that is targeted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishing often generates a cascade of indirect effects that can alter community structure, ecosystem function, and resilience. Lagged responses between trophic levels (e.g., herbivores and primary producers) can create nonlinear community dynamics by promoting thresholds and tipping points (Salomon et al, 2009), potentially triggering an abrupt regime shift to a degraded state (Frank et al, 2005; Österblom et al, 2007; Rassweiler et al, 2022). Our model reveals that resilience of corals on coral reefs is not only affected by the intensity at which fishers harvest herbivores but also by the type of herbivore that is targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Our main objective is to explore how fisher selectivity coupled with changes in catch alters the precariousness and reversibility of a coral-to-macroalgae regime shift. Our model is broadly grounded by the coral reef system of Moorea, French Polynesia, where there is detailed knowledge of the dynamics of the reef community (Adam et al, 2011(Adam et al, , 2014(Adam et al, , 2022Han et al, 2016;Holbrook et al, 2016Holbrook et al, , 2018Holbrook et al, , 2022Schmitt et al, 2019Schmitt et al, , 2022 and the small-scale reef fishery and fisher behavior (Holbrook et al, 2022;Lauer et al, 2022;Leenhardt et al, 2016;Nassiri et al, 2021;Rassweiler et al, 2020Rassweiler et al, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, browser biomass appears to be particularly susceptible to fishing on many coral reefs globally (Edwards et al 2014), a pattern that could be exacerbated in Moorea and elsewhere where local small‐scale fisheries disproportionately target species of browsers (Rassweiler et al 2020). Furthermore, movement patterns of fishers can further weaken resilience of the coral state after a large‐scale coral mortality event if fishers avoid macroalgae‐dominated areas and focus their fishing effort for herbivores on reefs that support the greatest remaining cover of coral (Rassweiler et al In press).…”
Section: Discussionmentioning
confidence: 99%
“…With decreased commercial fishing due to COVID‐19, we expect that there will be greater top‐down control this year compared to years when fishing pressures are higher. On the coral reefs of Moorea, seaweeds are controlled by herbivorous fishes (Adam et al, 2011 ) that are targeted by the local small‐scale fishery (Leenhardt et al, 2016 ; Rassweiler et al, 2020 ), and research has shown that intensification of fishing (Holbrook et al, 2016 ) and alteration of fisher behavior (Rassweiler et al, 2021 ) can reduce resilience of the coral state and promote a switch to seaweed dominated reefs that can represent a difficult‐to‐reverse, alternative basin of attraction (Schmitt et al, 2019 , 2021 ). Relaxation of fishing would strengthen resilience of coral communities to other disturbances such as storms and heat waves (Holbrook et al, 2016 ).…”
Section: Effects Of the Anthropause On Ecosystemsmentioning
confidence: 99%